The Influence of Environmental Management System, Capital Structure, Company Size, and Liquidity on the Company's Financial Performance - Sulistiani, Diah; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to empirically prove the influence of the environmental management system, capital structure, company size, and liquidity on the financial performance of companies in the energy sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The population in this study is energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. In this study, a purposive sampling technique was used by 14 companies so that the samples used were obtained a total of 42 observation data. This study uses multiple linear regression analysis using SPSS version 26 software as the calculation tool. Based on this study, the results show that the environmental management system, company size, and liquidity have no effect on the company's financial performance, while the capital structure has a negative effect on the company's financial performance. The predictive ability of the four variables on the financial performance of energy sector companies is 24% while the rest is from other variables.